Analysis of technological conditions influence on efficiency of oilfield treatment; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Usheva N. W. Natalia Wladimirowna; Moyzes O. E. Olga Efimovna; Kuzmenko E. A. Elena Anatolievna; Kim S. F.; Khlebnikova E. S. Elena Sergeevna; Dyalilova S. N.; Filippova T. V. Tatiana Vasilievna (Latest Researchers in Hydrocarbon Refining, 2015)
Title screen